The Influence of Entrepreneurial Literacy and Entrepreneurial Practice on Entrepreneurial Readiness In The Industrial Era 4.0 - Rini Rindrayani, Sulastri; Hairunisya, Nanis Hairunisya; Sudarmiani, Sudarmiani; Trisnantari, Hikmah Eva Trisnantari (Sumber Belajar Sejahtera, 2024)
Purpose - Industry 4.0 has brought about changes in a variety of fields, including education. Entrepreneurship education at the university level, in particular, must be capable of producing graduates capable of creating their employment opportunities and adapting to their surroundings. The purpose of this study is to describe and assess entrepreneurial practice learning and entrepreneurial literacy, as well as their impact on entrepreneurial readiness in the industry 4.0 era. Methodology - Responses were collected from 400 university students in Tulungagung Regency, East Java, who had taken the Entrepreneurship course. The students' responses were gathered using a questionnaire with Likert scale questions as the instrument. Findings - Data analysis using multiple linear regression revealed that entrepreneurial culture had a significant positive impact on preparation for entrepreneurship. Furthermore, entrepreneurial practice had a substantial positive impact on entrepreneurial readiness. Both entrepreneurial literacy and entrepreneurial practice significantly influenced entrepreneurial readiness. Significance - Entrepreneurial practice, in particular, made the greatest contribution to entrepreneurial readiness. This readiness can lead to the formation of long-term new ventures with the help of institutional infrastructure and business management guidance.